The Effect of Online Adminduk Service Applications on the Number of Population Administration Applications - ilahi, faidlul; saikin, saikin; ashari, maulana; fadli, sofiansyah (Universitas Trilogi, 2025)
This study aims to investigate the effect of using the population and civil registration office Online Service Application (SEMAIK) on the number of population administration (Adminduk) applications at the Population and Civil Registration Office (Disdukcapil) of Central Lombok Regency. The direct impact of the implementation of this application on the number of civil registration applications has not been widely studied empirically. Therefore, this research is important to determine the extent to which the use of the SEMAIK application has an effect on increasing applications for population administration services. The SEMAIK application, as an innovation of the Central Lombok Disdukcapil, is designed to make it easier for citizens to apply for civil registration documents online without the need to visit the Disdukcapil office directly. This research method uses the System Usability Scale (SUS) to assess the level of acceptance and satisfaction of application users. The study involved 48 respondents, resulting in an average SUS score of 73.9, which indicates that the application is in the “Acceptable” satisfaction category with a grade of C and a qualitative assessment between ‘Good’ to “Excellent”.”Data analysis shows that there is an increase in the number of Adminduk applications through the SEMAIK application during the 2021-2023 period, which is correlative with an increase in user satisfaction scores. This result confirms that the level of application acceptance is at a relatively good level. User satisfaction with the SEMAIK application has contributed to an increase in the number of Adminduk document submissions in Central Lombok Regency. This research provides important insights into the importance of usability in public service applications and its implications for the efficiency of population administration services.